Registration of 'Driver' hard red spring wheat. Issue 3 (1st September 2021) - Glover, K. D.; Kleinjan, J. L.; Graham, C.; Ali, S.; Byamukama, E.; Jin, Y.; Ingemansen, J. A.; Turnipseed, E. B.; Dykes, L.
Abstract: Widespread acceptance of new hard red spring wheat (HRSW; Triticum aestivum L). cultivars by South Dakota growers relies heavily on a favorable combination of essential production characteristics, such as agronomic performance, resistance to prominent diseases, and acceptable end‐use quality potential. Additional characteristics, however, such as lodging resistance are also important to growers. Steadily increasing levels of lodging resistance in new cultivar releases are a significant goal of the South Dakota State University (SDSU) HRSW breeding program. The objective of this research was to release a new HRSW cultivar with elevated resistance to lodging that is also capable of meeting grower expectations with respect to essential production characteristics. 'Driver' (Reg. no. CV‐1187, PI 698121) was developed by the SDSU‐HRSW breeding program and released by the South Dakota Agricultural Experiment Station (SDAES) to Certified seed producers in early 2020. The cross MN06075‐4/SD4165 was completed during spring 2011 and the resulting population was advanced via an early‐generation bulk‐testing program where F4:7 seed was included in the 2015 preliminary yield trial and designated as SD4625. Prior to release, SD4625 also was tested in the advanced yield trial from 2016 through 2019 as well as crop performance testing trials from 2017 through 2019. Driver was released for its combination of agronomic potential, disease resistance, acceptable end‐use quality, and lodging resistance.